Silicon carbide in catalysis: from inert bed filler to catalytic support and multifunctional material. Issue 1 (2nd January 2023) - Kulkarni, Shekhar R; Velisoju, Vijay K.; Tavares, Fernanda; Dikhtiarenko, Alla; Gascon, Jorge; Castaño, Pedro
ABSTRACT: Silicon carbide (SiC) or carborundum has unparalleled thermal stability and conductivity compared with many other materials. This feature together with its unique photoelectrical properties (tunable band gap: 2.39–3.33 eV), low thermal expansion, high strength, and good chemical and thermal stability makes it an ideal inert solid in catalysis. The evolution of methods for synthesizing SiC has also progressively endowed it with additional features at the multiscale. This review tracks the development of SiC from a secondary to a leading role material in catalysis. First, the intrinsic properties of SiC are discussed and compared with other state-of-the-art catalytic materials. The synthetic methods are systematically reviewed and compared. Then, the applications of SiC in catalysis are assessed, paying particular attention to those that involve C1 chemistry (Fischer–Tropsch Synthesis and the valorization of CO2 and CH4 ), photocatalysis and biomass conversion. Finally, the potential future applications of SiC are also addressed and discussed. Graphical Abstract: uf0001